Belawa as "Shasimi" in Kepri Islands - Ibnu, Cian; Zuraidah; Masyitah Novia Yanti; Aulia Chintara Wanda; Ayu Trianingsih (Social Impact Journal, 2023)
Indonesia is a maritime country scattered by islands; and archipelagos. Rich in cultural diversity ranging from ethnicity, tribe, race, and language. There are 17499 islands spread from Sabang to Merauke, hundreds of regional languages, ​​and many customs of various regions. This study aims to reveal the existence of a typical coastal culture of the islands, namely the culture of processed raw squid fish. The habit of consuming processed raw fish is certainly familiar to both traditional and modern communities. Consumption of raw fish has been widely found in various places in the world in Asia, Japan there is sashimi, in Europe, namely Spain there is Ceviche de Calamares, in Korea there is Sannakji, and in Thailand, there is Larb Pla Muk. The approach used in this study is a descriptive-qualitative study with a special case regarding culinary in Mensanak Village, Kitang Bidare District, Lingga Regency, Riau Islands Province. This village with a small community inherits coastal culture, and fishermen as the main livelihood of the local community in the Riau Islands region. The results of this study found that there is a habit of consuming raw fish made from squid mixed with natural spices and processed in a traditional way, they call it belawa, which is processed raw squid.